2017
DOI: 10.1038/sc.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of androgen deficiency in chronic spinal cord injury patients suffering from erectile dysfunction

Abstract: Tehran University of Medical Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We observed that SCI patients who were smoking had low testosterone levels as compared to non-smokers; however, we also observed that smoking was not an independent predictor of testosterone levels. Behnaz et al also observed that smoking was not an independent predictor of testosterone level [24].…”
Section: Discussionmentioning
confidence: 94%
“…We observed that SCI patients who were smoking had low testosterone levels as compared to non-smokers; however, we also observed that smoking was not an independent predictor of testosterone levels. Behnaz et al also observed that smoking was not an independent predictor of testosterone level [24].…”
Section: Discussionmentioning
confidence: 94%
“…We applied both the paired t-test and multilevel mixed model using random intercept and residual maximum likelihood estimation to determine the longitudinal changes in androgens across the period of inpatient rehabilitation. The model was adjusted for age, BMI, level of injury, completeness of injury, time since injury, opioids use, and corticosteroids use in [ 32 ]. All analyses were stratified according to sex and were performed using Stata 16.1 (StataCorp LLC, College Station, TX, USA) for Windows.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of some spared long ascending and descending propriospinal pathways responsible for interlimb coordination can alter neural circuitry at the lumbosacral level, providing a potential mechanism through which forelimb exercise may affect BSM burst duration. In relation to the PDFR, decreases in latency and burst duration suggest increased local reflex synaptic efficacy, where the longer onset of PDFR suggests increased descending tonic inhibition.Serum testosterone is known to decline after SCI and may play an additional role in sexual dysfunction apart from neurological deficits[173,174,[203][204][205]. After SCI in the current study, rats had a significant decrease in urine testosterone levels that remained depressed for the duration of the study.…”
mentioning
confidence: 57%
“…As ex copula sexual reflexes can pertain to multiple aspects of sexual responses in the rat animal model, and these reflexes can be elicited through multiple different methodologies, we felt it best to use the term "penile dorsiflexion reflex" (PDFR) as it is all encompassing of this particular sexual reflex elicited in this particular method as a whole. Additionally, because testosterone levels are known to decrease after SCI [173,174], levels were periodically examined to determine if there was an effect of ABT. behavioral assessments (see below) were conducted at regular intervals throughout the study.…”
Section: Potential Therapeutic Target For Recovery Of Sexual Functionmentioning
confidence: 99%